Advanced and Readily‐Available Wireless‐Powered Blue‐Light‐Implant for Non‐Invasive Peri‐Implant Disinfection - Ludan Zhang; Yamin Li; Lintian Yuan; Qianyi Zhang; Yuqing Yan; Fan Dong; Jun Tang; Yuguang Wang (Advanced Science)
Abstract Non‐invasive light‐based antibacterial therapy has a good prospect in non‐surgical treatment of peri‐implant infections. However, its applications are severely limited by poor penetration of light into human tissues, leading to unsatisfying outcomes. Moreover, as an essential prerequisite for traditional light therapy, lasers can no longer meet the patients’ needs for convenient treatment at any time. To break through the spatial and temporal limitations of traditional light therapy, a wireless‐powered blue‐light zirconia implant for readily available treatment of peri‐implant infection is proposed. In space, complete irradiation to complex peri‐implant structure is realized by the built‐in wireless‐powered light source, thus improving the efficacy. In time, wireless‐powering allows timely and controllable anti‐infection treatment. Blue micro‐light emitting diodes are used as therapeutic light sources, which effectively kill peri‐implant infection‐related bacteria without exogenous photosensitive agents. Porphyromonas gingivalis biofilm on implant surface can be completely killed after 20 min irradiation in vitro. The bactericidal rate of peri‐implant methicillin‐resistant Staphylococcus aureus infection reaches 99.96 ± 0.03% under 30 min per day blue light exposure in vivo. Within the scope of this study, the treatment of peri‐implant infection with blue‐light implant has preliminary feasibility, giving a new approach to non‐invasive treatment of deep oral infections, including peri‐implant infections.